Y-16=11(x-1)

Simple and best practice solution for Y-16=11(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-16=11(x-1) equation:


Simplifying
Y + -16 = 11(x + -1)

Reorder the terms:
-16 + Y = 11(x + -1)

Reorder the terms:
-16 + Y = 11(-1 + x)
-16 + Y = (-1 * 11 + x * 11)
-16 + Y = (-11 + 11x)

Solving
-16 + Y = -11 + 11x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + Y = -11 + 16 + 11x

Combine like terms: -16 + 16 = 0
0 + Y = -11 + 16 + 11x
Y = -11 + 16 + 11x

Combine like terms: -11 + 16 = 5
Y = 5 + 11x

Simplifying
Y = 5 + 11x

See similar equations:

| b^4-5b^2-6b=0 | | .77=(1/x) | | x^4+9x^2+4=0 | | .77=1/x | | x/24-1.4=8.3 | | (X+4)-x-(5-6x)=11 | | Y=(6x+3)10 | | 8x+6y=-26 | | 2a+4(2-a)-6(1+a)=18 | | m+(-6)=22 | | 15+4ln(x)=10 | | Z-19=19 | | 2(x+6)=-2x(x-4) | | 5.25=1.25 | | 5[x+9]=80 | | Y=5.5x+15 | | X+0.5y=7 | | 3C+7+5c=4c+31 | | 8x+-2=60 | | 6x+2=8x-26 | | (3x+4)(x^2+14x+40)=0 | | 5/2u=20 | | 5i/8-3i | | 2(i+2)-9=-17-i | | 7x/2=(5x-4)/3 | | ln(x)+ln(x+-6)=ln(8x-24) | | 15x^2+x=75 | | -105=-7(2k+1) | | (x+3)+2=0 | | 11x-2+6x+7=90 | | (3y+5)+(2x+1)=85 | | 28-42=154 |

Equations solver categories